2001
DOI: 10.1002/1521-396x(200108)186:3<487::aid-pssa487>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

The Native Oxide Effects on the Optical Properties of TbFe2

Abstract: The native oxide effects on the optical properties of a polycrystalline TbFe 2 were studied using spectroscopic ellipsometry and the grazing-incident X-ray reflectivity technique. The spectra of the dielectric functions for the TbFe 2 sample exposed to air at room temperature were measured, as the sample was oxidized. The spectra of the reflectance, optical conductivity, and skin depth were obtained in a 12 h interval. As the thickness of the oxide layer gets larger, the magnitude of the optical conductivity d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…It has been shown that as the thickness of the oxide layer is reduced, the magnitude of the optical conductivity increases and the features in the optical conductivity spectrum become more prominent. 8 The dc resistivity results for all films in the series are shown in Fig. 6.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that as the thickness of the oxide layer is reduced, the magnitude of the optical conductivity increases and the features in the optical conductivity spectrum become more prominent. 8 The dc resistivity results for all films in the series are shown in Fig. 6.…”
Section: Resultsmentioning
confidence: 99%